COMMUNICATION’S IMPACT ON TEAM COLLABORATION IN CULINARY AND TOURISM ENTERPRISES - Agrina, Viola Daspi; Ariza, Putri Rizkika; Glory, Juda Boni; Melanda; Maldin, Siska Amelia (JURNAL MANAJEMEN KULINER, 2025)
This study aims to analyze the influence of communication on teamwork in the tourism and culinary business sectors. Using a qualitative descriptive approach, data were collected through literature studies and analyzed using thematic interpretation. The results indicate that effective communication supports task coordination, fosters innovation, and enhances team productivity. In tourism and culinary businesses, communication strategies such as integrated marketing communication and digital promotion also play a significant role in external collaboration and market competitiveness. Strong internal teamwork, backed by well-structured communication, is a critical factor for business sustainability.